The adherence to effective vaccine stock management protocols in the government facilities, the availability of vaccines, and the effectiveness of the stock visibility system in OR Tambo District of the Eastern Cape Province of South Africa - Iwu, Chinwe Juliana (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.